Foliar Fe2O3 nanoparticles enhance cadmium tolerance in Amaranthus hypochondriacus by modulating cell wall immobilization and antioxidant defenses - Yanfeng Hu; Jia You; Yue Xiang; Runze Tian; Jianli Wang; Zhongbao Shen; Yansheng Li (Environmental Chemistry and Ecotoxicology, 2025)
The integration of nanotechnology with high biomass plants offers a sustainable strategy for rehabilitating cadmium (Cd)-contaminated lands. However, the potential of iron-based nanoparticles (Fe-NPs) to enhance Cd phytoremediation in the hyperaccumulator Amaranthus hypochondriacus remains unclear. The current study demonstrates that foliar spraying of 100 mg L−1 Fe-NPs (α-Fe2O3) alleviated Cd (10 mg kg−1)-induced growth inhibition (plant height, leaf area, and biomass), and partially restored leaf photosynthetic parameters and chloroplast morphology. Fe-NPs also reduced Cd-triggered oxidative damage by decreasing reactive oxygen species (ROS) and malondialdehyde (MDA) levels while enhancing antioxidant activities in leaves. Moreover, Fe-NPs treatment significantly increased Cd accumulation in leaves and total Cd extraction, indicating enhanced phytoremediation efficiency. Meanwhile, Fe-NPs modified the subcellular Cd distribution in leaves, increasing cell wall Cd fixation from 56.8 % to 61.57 %. Transcriptomic analysis revealed that Fe-NPs + Cd treatment induced the most differentially expressed genes (1097 upregulated, 572 downregulated), mainly enriched in DNA-binding, protein catalysis, chloroplast function, cell wall dynamics, metal ion binding. Notably, Fe-NPs upregulated a group of wall-associated receptor-like kinase (WAKL) genes that were downregulated by Cd. Furthermore, AhWAKL16 overexpression in hairy roots significantly increased cell wall Cd content by 14 % and mitigated Cd-induced root elongation inhibition and MDA accumulation. This work highlights the potential of Fe-NPs for Cd remediation in A. hypochondriacus, and provides the first evidence that Fe-NPs enhance Cd tolerance, at least partially, through WAKL-mediated Cd immobilization in the cell wall.